2016
DOI: 10.3389/fmicb.2016.01827
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Typhimurium and Multidirectional Communication in the Gut

Abstract: The mammalian digestive tract is home to trillions of microbes, including bacteria, archaea, protozoa, fungi, and viruses. In monogastric mammals the stomach and small intestine harbor diverse bacterial populations but are typically less populated than the colon. The gut bacterial community (microbiota hereafter) varies widely among different host species and individuals within a species. It is influenced by season of the year, age of the host, stress and disease. Ideally, the host and microbiota benefit each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 169 publications
(218 reference statements)
0
40
0
Order By: Relevance
“…Notably, the main mechanism used by Salmonella to adapt to environmental conditions during the initial passage through the host gut are encoded in the core genome, which acts independent of the genes acquired by HGT, including the virulence genes encoded in SPIs. These regulatory systems encoded within these SPIs comprise, among others, the activation of ATR systems [41][42][43], systems related to survival under limitation of nutrient step [44,45], tolerance to hyperosmolarity and anaerobic environments [46][47][48], as well as quorum sensing [49]. Although initially these systems are responsible for the adaptation to the adverse intestinal environment of the host, some of them (such as the two-component systems PhoPQ and PmrAB, or the OmpR protein) are also responsible for the activation of genes encoded within the pathogenicity islands and other HGT elements, to ensure the passage through the intestinal barrier [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the main mechanism used by Salmonella to adapt to environmental conditions during the initial passage through the host gut are encoded in the core genome, which acts independent of the genes acquired by HGT, including the virulence genes encoded in SPIs. These regulatory systems encoded within these SPIs comprise, among others, the activation of ATR systems [41][42][43], systems related to survival under limitation of nutrient step [44,45], tolerance to hyperosmolarity and anaerobic environments [46][47][48], as well as quorum sensing [49]. Although initially these systems are responsible for the adaptation to the adverse intestinal environment of the host, some of them (such as the two-component systems PhoPQ and PmrAB, or the OmpR protein) are also responsible for the activation of genes encoded within the pathogenicity islands and other HGT elements, to ensure the passage through the intestinal barrier [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Moving to a whole-animal infection model (pigs), supplementation of the diet with a mixture of organic acids including propionate resulted in decreased Salmonella recovery from the mesenteric lymph nodes [64]. Thus, simple dietary supplementation with SCFAs, especially propionate, may be a promising intervention strategy for decreasing Salmonella infection in farm animals [65]. Interestingly, it has also been suggested that the production of propionate by intestinal microflora may be a protective mechanism to control the host response to commensals.…”
Section: Propionate Metabolism As An Antimicrobial Targetmentioning
confidence: 99%
“…In addition, the QseB regulator of the host's normal flora is also recognized for epinephrine, norepinephrine and neurotransmitter. This system induces the SPI-2 gene expression to support Salmonella survival in macrophage, as well as facilitates the expression of gene encoded on SPI-1 and SPI-3 (Bearson & Bearson, 2008;Gart et al, 2016;Morei, Weinshenker & Sperandio, 2010) In this present work, the sdiA and luxS only, were chosen for the QS genes by interfering with the expression of these genes with CFCS. They have clear known signaling pathways, and are associated with the critical induction of SPI genes.…”
Section: Discussionmentioning
confidence: 99%